Design and development of a third-person futuristic adventure game (C) - Tan, Fang Tian (2018)
The gaming industry has been progressively developing. Beginning with simple game systems running on computers with limited random-access memory, it has grown into games with realistic graphics and sophisticated algorithms running based on advanced technologies. Due to the steady growth and increasing popularity in computer and video games, it has been increasingly challenging for developers to build games that are constantly compelling to their target audiences. The primary purpose of the final year project is thus to design and develop a high-action action or adventure game based on the recent trends in the game industry. This project is a collaboration among 4 members – Ocampo Jessica Anne Pare, Liang Wen Jun, Daniel Kurniadi. The author is solely in charge of the main character development. This includes Character Modelling, and the implementation of Game Mechanics related to the Main Character. This report would provide a concise and vivid account of the author’s efforts and achievement through the one-year Final Year Project.